Shifting Meaning of Sekaten in the Modern Era - Saifi Nurul Jannah (Javanologi: International Journal of Javanese Studies, 2024)
This article contains changes in the meaning of the sekaten tradition from time to time, especially in this modern era. Data was obtained through a descriptive qualitative research method which is a natural research and the data produced is descriptive. The research is expected to be able to reveal the shift in the meaning of sekaten in the current era. The results of this study obtained that the sekaten upacra comes from the da'wah method carried out by the guardians and the symbols used in the sekaten traditional ceremony have Javanese Philosophy values. Through ritual symbols, the meaning contained is communicated by the community in a sustainable manner even though the times have changed, not changing the original meaning of the sekaten ceremony. Through this ceremony, a communication ritual process occurs so as to pass on the understanding of the meaning of good values to the community. The conclusion of this study shows that the Sekaten Ceremony is a complex cultural practice, which combines elements of Islamic beliefs, community interaction, and the transmission of traditional values and practices. These traditions are a testament to the region's rich cultural heritage and the continued importance of these traditions in people's lives.